Family members in a long dream series - Schredl, Michael (International journal of dream research, 2021)
Family members appear within dreams quite often, a finding that is in accordance with the continuity hypothesis of dreaming and the Social Simulation theory. Within a series of 2,025 dreams recorded over more than 30 years by a female dreamer, they were examined to determine how frequently family members occurred over time in her dreams. Overall, the findings indicate that family members were quite common in her dreams, with the mother appearing with the highest frequency. The frequency of the dreams with most family members decreased over time, supporting the hypothesis that childhood/adolescence experiences (closest family bonds) appear less often in dreams as the dreamer is getting older. The frequency of the dreams that included the mother decreased after her death, also supporting the continuity hypothesis of dreams. For testing the strengthening hypothesis of the Social Simulation Theory, it would be very interesting to study whether the frequency of dreams of a particular family member is associated with an increase in closeness over time.
Gesehen am 02.11.2021